Continuity Of Care Of Mrs. D During Preconception, Term I, II And III Of Pregnancy, Labour, Postpartum, Newborn And Family Planning Services In Pmb Kurao Padang - Yulizawati Yulizawati; Miranie Safaringga; Iney Pive Enosentris (Universitas Andalas, 2022)
Maternal Mortality Rate is the ratio of maternal mortality during pregnancy, childbirth and postpartum caused by pregnancy, childbirth, and postpartum in every 100,000 live births. The maternal mortality rate (MMR) in the world in 2015 was estimated at 216 per 100,000 live births or an estimated 303,000 deaths. The target of the 2030 Sustainable Development Goals (SDGs) is to reduce the Maternal Mortality Rate (MMR) below 70 per 100,000live births. The RPJMN target in 2019 is 306 per 100,000 live births (Ministry of Health, 2019). Meanwhile, the IMR in the world is 10,000,000 people per year. IMR in Indonesia reaches 22 per 1,000 live births. The purpose ofmidwifery continuity of care is to provide continuous care starting from the preconception period, pregnancy, childbirth, postpartum and family planning. The research method is a description, the form of case study research,the subject of pregnant women Mrs. D is 26 years old at PMB with Kurao. The technique of collecting data is by interviewing and observing (observation) and using data analysis techniques in the field. The instruments used in this study were the format of midwifery care, interviewguidelines, examination tools and the MCH Handbook. The results showed that the care given to Mrs. D is 26 years old starting from the preconception period, pregnancy, childbirth, postpartum, and newborn and family planning is going well, the mother and baby are in good health. In conclusion, midwifery continuity of care provided with care starting from pregnancy, childbirth, postpartum, and newborns can provide benefits to mothersand babies in the process. Continuity of care midwifery care can optimize the detection of high-risk maternal and neonatal.